WARTOŚĆ PRZESTRZENI MIESZKANIOWEJ WYRAZEM POSTRZEGANIA WALORÓW KRAJOBRAZOWYCH NA PRZYKŁADZIE OLSZTYNA - Senetra, Adam; Szczepańska, Agnieszka (Space – Society – Economy, 2012)
The concept of landscape is associated primarily with visual perception, but landscape amenities can be also perceived by other senses, including the hearing, smell and touch (multisensory perception). According to available data, the visual landscape and the aural landscape complement each other (visual sensations are accompanied by aural stimuli). In urbanized areas, property value is affected by both the visual and aural perception of scenery attributes. The prices of real estates located within one residential complex or several neighboring complexes may vary widely. The results of our previous study show that one of the reasons for differences in real estate prices is the quality of green spaces which play a key role in landscape perception. The above is observed particularly in the living environment, including housing areas, where people spend long periods of time. The objective of this study was to validate our previous findings and to determine the effect of street noise intensity on the prices of residential premises (multi-family housing) on the local real estate market. The studied dataset was homogeneous in terms of the location and type of property, but it differed with respect to landscape values (access to green areas, noise level). The visual and aural perception of landscape by potential homebuyers affected their assessment of residential space. The analysis covered a multi-family housing estate located in the city of Olsztyn. The results were interpreted in view of purchase-and-sale transactions of residential premises concluded in 2009–2010 (involving cooperative ownership titles), landscape evaluation by a quantitative classification method, and the acoustic map developed for the city.